US President Barack Obama’s higher education reform plans on financial supports = Kế hoạch cải cách hỗ trợ tài chính giáo dục đại học của Tổng thống Mỹ Barack Obama - Nguyễn, Lê Hường (2020)
In Vietnam, research on the US higher education system has been introduced to the scholars as well as the public. However, there has been not much research that intensely focuses on higher education under the time of Barack Obama, especially after his reelection in 2012. As one of the first attempts, this research paper seeks to explore the higher education reform plans of President Obama and its details, implementation and responses, especially on federal financial supports. The paper begins with reviewing the remarkable features of the US Higher Education system and important historical legislations that make profound impacts to the US Higher Education system until today. Then, the investigation involves the legislations and their implementation under President Obama’s first term 2009-2012 and the reform plans for the second term 2012-2015. The analyses of the collected data demonstrate improvements of the President’s plans from previous financial policies; its strengths and challenges from scholars’ perspectives in order to discuss the plan’s possibility of success and its impacts.